Halal topic journal content analysis in Journal of Islamic Marketing, British Food Journal and Meat Science / Muslim Ismail@Ahmad ...[et al.] - Ismail@Ahmad, Muslim; Ismail, Mohd Nasir; Othman, Roslina; Ismail, Mohd Saufi (2019)
Journal of Islamic Marketing, British Food Journal and Meat Science are among the most productive journals publication in halal research. Data collection is from Scopus database, set for all available documents in each respective journals. Dataset in Journal of Islamic Marketing was 280 citations from 2010 to 2019. British Food Journal data (from 2010-2019) was 1,361 citations and Meat Science data was 1,852 citations (from 2014- 2019). Scopus’s CiteScore, SCImago Journal Rank (SJR) and Source Normalized Impact per Paper (SNIP) is used to measure the journals. Papers of the highest citation each of respective journals from 2016-2018 are highlighted. This research utilizes VOSviewer for data visualization and GEPHI for data statistical analysis of words co-occurrence in titles and abstracts.. This research aims to analyse content in three journals specifically to identify subject relations or subject clusters in the article journals in 8 years span